The psychological impact of undergoing genetic‐risk profiling in men with a family history of prostate cancer. Issue 11 (14th April 2015) - Bancroft, Elizabeth K.; Castro, Elena; Bancroft, Gordon A.; Ardern‐Jones, Audrey; Moynihan, Clare; Page, Elizabeth; Taylor, Natalie; Eeles, Rosalind A.; Rowley, Emma; Cox, Karen
Abstract: Background: The ability to identify men at genetically high‐risk of prostate cancer (PrCa) would enable screening to be targeted at those most in need. This study explored the psychological impact (in terms of general and PrCa‐specific worry and risk perceptions) on men with a family history of PrCa, undergoing prostate screening and genetic‐risk profiling, within a research study. Methods: A prospective exploratory approach was adopted, incorporating a sequential mixed‐method design. Questionnaires were completed at two time points to measure the impact of undergoing screening and genetic‐risk profiling. In‐depth interviews were completed in a subgroup after all study procedures were completed and analysed using a framework approach. Results: Ninety‐five men completed both questionnaires, and 26 were interviewed. No measurable psychological distress was detectable in the group as a whole. The interview findings fell into two categories: 'feeling at risk' and 'living with risk'. The feeling of being at risk of PrCa is a part of men's lives, shaped by assumptions and information gathered over many years. Men used this information to communicate about PrCa risk to their peers. Men overestimate their risk of PrCa and have an innate assumption that they will develop PrCa. The interviews revealed that men experienced acute anxiety when waiting for screening results. Conclusions: Personalised genetic‐risk assessments do not prevent men from overestimating their risk of PrCa. Screening anxiety is common, and timeframes for receiving results should be kept to a minimum. Methods of risk communication in men at risk of PrCa should be the subject of future research. Copyright © 2015 John Wiley & Sons, Ltd.